Balance Scorecard Sebagai Pengukur Kinerja Manajemen Ditinjau Dari Perspektif Keuangan - Hamida, Novelia; Aulia, Citra; Siregar, Kholila Yuli Yanti; Barus, Muhammad Joni (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2023)
This study aims to analyze the implementation of Balanced Scorecard as a management performance measurement tool at UD. Devi, with a focus on the financial aspect. This research adopts a qualitative approach by applying data collection techniques in the form of interviews, observations, and document studies. The main respondents in this group are stakeholders at the leadership level of UD. Devi, who are directly involved in the process of implementing and using the Balanced Scorecard. In the context of UD. Devi, the implementation of BSC has a positive impact on measuring management performance. The holistic approach, open communication, active participation of all relevant parties, regular evaluation, and in-depth contribution of financial aspects have been key factors in the successful implementation of BSC.